Impact of MgO Nanofluid Concentration on Thermal and Electrical Efficiency of PV/T Systems: A CFD and Experimental Study - Bryan Amrizha; Avita Ayu Permanasari (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
This study investigates the effect of Magnesium Oxide (MgO) nanofluid concentration on the thermal and electrical efficiency of photovoltaic thermal (PV/T) systems using both experimental characterization and Computational Fluid Dynamics (CFD) simulation. Inlet flow rates (0.5–2.5 L/min) and MgO volume fractions (0.08%–0.4%) were varied. Experimental results confirm nanofluid stability for over 15 days at concentrations up to 0.2 vol%. CFD simulations using ANSYS Fluent reveal that the highest collector thermal efficiency of 69.1% is achieved at 0.2 vol% and 1.5 L/min, which is 16.7% higher than when using distilled water (DW) or ethylene glycol (EG) alone. The absorbed energy factor increases by 16.74%, while heat loss decreases by 52.2%. These findings highlight the significant performance gains attainable through optimized MgO nanofluid use in PV/T systems.